IMPROVING STUDENT ACHIEVEMENT IN A BEAUTIFUL ENVIRONMENT AT AL-AZHAR MEDAN'S LEADING HIGH SCHOOL - Mahirah Azfina Harahap; Nazilah Ramadhani; Rafa Arya Dilla; Alfinza Rajad Husein (PT. Radja Intercontinental Publishing, 2025)
The problem that will be studied in this journal is the influence of the beautiful environment in Al-Azhar Medan's Top High School. The approach used in this journal is a qualitative research approach by filling out a questionnaire from active students of Al-Azhar Medan High School. The number of participants in this study was 37 students. The purpose of this study was to determine the influence of the beautiful environment on learning at Al-Azhar Medan High School. This study will prove whether a beautiful school environment will affect learning and how beautiful Al-Azhar Medan High School is.